2017
DOI: 10.1155/2017/4563826
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Characterization of Second-Line Drugs Resistance among Multidrug-ResistantMycobacterium tuberculosisIsolates in Southwest of China

Abstract: This study aimed to investigate the prevalence of multidrug-resistant tuberculosis (MDR-TB) isolates resistant to the second-line antituberculosis drugs (SLDs) and its association with resistant-related gene mutations in Mycobacterium tuberculosis (M.tb) isolates from Southwest of China. There were 81 isolates resistant to at least one of the SLDs among 156 MDR-TB isolates (81/156, 51.9%). The rates of general resistance to each of the drugs were as follows: OFX (66/156, 42.3%), KAN (26/156, 16.7%), CAP (13/15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…The present findings revealed that 48.2% (124/257) were resistant to at least one five SLD. Previously, several studies reported the resistance rate of SLD strains has been estimated to range from 25.7 to 51.9% (Bakuła et al, 2016; Brossier et al, 2017; Hu et al, 2017). According to a recently published World Health Organization (WHO) report, among cases of MDR-TB in 2017, 8.5% ( 95%CI , 6.2–11.0%) were estimated to have XDR-TB (World Health Organization [WHO], 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings revealed that 48.2% (124/257) were resistant to at least one five SLD. Previously, several studies reported the resistance rate of SLD strains has been estimated to range from 25.7 to 51.9% (Bakuła et al, 2016; Brossier et al, 2017; Hu et al, 2017). According to a recently published World Health Organization (WHO) report, among cases of MDR-TB in 2017, 8.5% ( 95%CI , 6.2–11.0%) were estimated to have XDR-TB (World Health Organization [WHO], 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2 The emergence of multidrug-resistant TB (MDR-TB) 3 and extensively drug-resistant tuberculosis (XDR-TB) 4 has made the battle against TB more difficult because most currently available therapeutic options are ineffective against these resistant strains. 5 Furthermore, the appearance of totally drug-resistant (TDR) strains has heightened this challenge because these strains are unaffected by the currently available anti-TB agents. 6 Thus, developing novel therapeutic agents that are capable of combating resistant strains of MTB is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing prevalence of TB in the form of multi-drug-resistant (MDR)-TB [ 2 ] and extensively drug-resistant (XDR)-TB [ 3 ] has triggered the necessity for more effective therapeutic regimens with fewer side effects. Treating and managing MDR-TB and XDR-TB has proven to be more challenging, as second-line drugs have largely become less effective [ 4 ]. This problem has been made worse by the emergence of totally drug-resistant (TDR) strains of MTB [ 5 ], which do not respond to anti-TB drug treatments.…”
Section: Introductionmentioning
confidence: 99%